(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper deals with the brush slip ring contact modeling. Approaches the sliding contact problem with the synergy theory. The contact layer is considered using mechanical, electrical and thermal properties. The simulation model includes algorithms of: - generation of microscale contact surface, - approachment of two surfaces, - fritting and breakdown effects of oxide layer, - extracting clusters of conducting area, - calculating constriction resistance using fractal dimensionality, - generation of heat caused by electrical current and mechanical friction, - calculation of integral characteristics. The program implementing the model may be used to optimize the contact materials before time-consuming and expensive tests. Finally discusses the implemented model and its results, problems of verification and validation.